Molecular simulation studies of hydrocarbon and carbon dioxide adsorption on coal - Zhang, J.; Liu, K.; Clennell, M.; Dewhurst, D.; Pan, Z.; Pervukhina, Marina; Han, T. (2015)
© 2015, The Author(s). Sorption isotherms of hydrocarbon and carbon dioxide (CO2) provide crucial information for designing processes to sequester CO2 and recover natural gas from unmineable coal beds. Methane (CH4), ethane (C2H6), and CO2 adsorption isotherms on dry coal and the temperature effect on their maximum sorption capacity have been studied by performing combined Monte Carlo (MC) and molecular dynamics (MD) simulations at temperatures of 308 and 370 K (35 and 97 °C) and at pressures up to 10 MPa. Simulation results demonstrate that absolute sorption (expressed as a mass basis) divided by bulk gas density has negligible temperature effect on CH4, C2H6, and CO2 sorption on dry coal when pressure is over 6 MPa. CO2 is more closely packed due to stronger interaction with coal and the stronger interaction between CO2 molecules compared, respectively, with the interactions between hydrocarbons and coal and between hydrocarbons. The results of this work suggest that the “a” constant (proportional to Tc 2/Pc) in the Peng–Robinson equation of state is an important factor affecting the sorption behavior of hydrocarbons. CO2 injection pressures of lower than 8 MPa may be desirable for CH4 recovery and CO2 sequestration. This study provides a quantitative understanding of the effects of temperature on coal sorption capacity for CH4, C2H6, and CO2 from a microscopic perspective.